APPLICATIONS OF ARTIFICIAL INTELLIGENCE IN AGRICULTURE - Ankit Kumar, Sofia Kumarswamy Pillai (International Journal of Modern Agriculture, 2021)
Agriculture is greatest systematic term use to describe various forms with which crops plant as well as domestics animal provide food as well as other goods to the world's human population. Artificial Intelligence (AI) has recently made an appearance in the agriculture sector. Unsuitable soil management, diseases as well as pest infestations, large data requirement, poor productivity, as well as a information gap between farmer as well as technologies are only a few of the challenges the sector faces in order to increase its production. This paper gives all details about artificial intelligence as well as agriculture. This paper also contain applications of artificial intelligence, robots in artificial intelligence, architecture of artificial neural network in artificial intelligence as well as irrigation using artificial intelligence. Artificial intelligence (AI) can be used to forecast demas well as by studying factors such as demographic rise, historical demas well as trends for food resources, as well as regional main food patterns, among others. This knowledge may be use to effectively change harvesting habits, as well as reduce crop yield waste as well as improve farmer incomes.